2019
DOI: 10.18632/aging.101905
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline, Azithromycin and Vitamin C (DAV): A potent combination therapy for targeting mitochondria and eradicating cancer stem cells (CSCs)

Abstract: Here, we devised a new strategy for eradicating cancer stem cells (CSCs), via a “synthetic-metabolic” approach, involving two FDA-approved antibiotics and a dietary vitamin supplement. This approach was designed to induce a “rho-zero-like” phenotype in cancer cells. This strategy effectively results in the synergistic eradication of CSCs, using vanishingly small quantities of two antibiotics. The 2 metabolic targets are i) the large mitochondrial ribosome and ii) the small mitochondrial ribosome. Azithromycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 31 publications
(38 reference statements)
1
56
0
Order By: Relevance
“…A triple combination therapy using lower doses of two clinically approved drugs-Doxycycline and Azithromycin-at a concentration of 1 µM and a dosage of Vit.C of 250 µM, showed a complete eradication of CSC propagation [20] (Figure 2). The synergistic effect of these compounds on the breast cancer cell line MCF7 were induced by the inhibition of two key targets, namely the large (39 s) and small mitochondrial ribosomes (28 s).…”
Section: Synergetic Effect Of Vitc On Energy Metabolism In Cancer Stmentioning
confidence: 93%
See 2 more Smart Citations
“…A triple combination therapy using lower doses of two clinically approved drugs-Doxycycline and Azithromycin-at a concentration of 1 µM and a dosage of Vit.C of 250 µM, showed a complete eradication of CSC propagation [20] (Figure 2). The synergistic effect of these compounds on the breast cancer cell line MCF7 were induced by the inhibition of two key targets, namely the large (39 s) and small mitochondrial ribosomes (28 s).…”
Section: Synergetic Effect Of Vitc On Energy Metabolism In Cancer Stmentioning
confidence: 93%
“…Although Vit.C generally acts as an antioxidant, due to its relative concentration and cellular localization, they acted as a mild pro-oxidant and stimulated free radical production leading to mitochondrial biogenesis in addition to mitochondrial oxidative stress. However, in this study no Vit.C inhibiting glycolysis via inhibiting glycolytic enzyme GAPDH was observed [20].…”
Section: Synergetic Effect Of Vitc On Energy Metabolism In Cancer Stmentioning
confidence: 99%
See 1 more Smart Citation
“…The varying localization of SLC23A2 in cells may be important for helping increase the therapeutic effect of vitamin C, as its mitochondrial localization in most cancer cell lines has allowed for mitochondria to be targeted in cancer therapeutics [238]. A recent study showed that a combinatorial therapy of doxycycline, azithromycin, and vitamin C effectively eradicates cancer stem cells [239]. Similarly, a combination treatment of vitamin C and cetuximab was recently shown to be an effective treatment to limit the development of acquired resistances in colorectal cancer, slowed the growth of cancerous cells, and impaired the structure of organoids [240].…”
Section: Vitamin Transporters In Cancermentioning
confidence: 99%
“…It was argued that the observed effect was due to synthetic lethality induced by the combined treatment in that doxycycline targeted mitochondrial respiration and vitamin C-glycolysis. The effectiveness of the combined treatment with doxycycline and vitamin C in cancer by targeting mitochondria was confirmed in subsequent studies in which azithromycin was also applied [119].…”
Section: Cancer Stem Cellsmentioning
confidence: 83%